Case Report: A case of COL1A1–PDGFB fusion uterine sarcoma at cervix and insights into the clinical management of rare uterine sarcoma - Lu, Linghui; Wang, Shunni; Shen, Haoran; Zhang, Feiran; Ma, Fenghua; Shi, Yue; Ning, Yan (Frontiers in Oncology, 2023)
COL1A1–PDGFB gene fusion uterine sarcoma is an especially rare malignant mesenchymal tumor that was previously classified as an undifferentiated uterine sarcoma due to the lack of specific features of differentiation. Till now, only five cases have been reported, and here we presented another case recently diagnosed in a Chinese woman who had vaginal bleeding. She presented with a cervical mass at the anterior lip of the cervix invading the vagina and was treated with laparoscopic total hysterectomy plus bilateral salpingo-oophorectomy (TH+BSO) and partial vaginal wall resection with the final pathology of COL1A1–PDGFB fusion uterine sarcoma. Our aim is to emphasize the importance of differential diagnosis of this rare tumor, as early precise diagnosis may allow patients to benefit from the targeted therapy imatinib. This article also serves as further clinical evidence of this disease, serving to increase clinical awareness of this rare sarcoma to avoid misdiagnosis.